Ictiofauna de estuários da região semiárida do Brasil: inventário de espécies, aspectos funcionais e influência de evento climático - Lourenço, Ronaldo César Gurgel (2023)
Most estuaries of the 'Northeast of Brazil' marine ecoregion are seasonally hypersaline, and are prone to extreme weather events that can modify community of the fish composition. It is urgent to understand community responses to different environmental gradients in order to predict the effects of climate change on estuaries influenced by the semi-arid climate of Northeast Brazil. The present study carried out an inventory of fish species in these estuaries (Chapter 1), described fish assemblages in terms of rarity and functional redundancy (Chapter 2), and investigated taxonomic and functional patterns based on different salinity gradients and climatic seasons Chapter 3). The fish fauna was sampled in a standardized way between 2014 and 2020. The species were classified according to diet, use of the estuary, reproduction, position in the water and mobility. Morphometric measures also characterized food acquisition, locomotion and habitat use. Taxonomic rarities (restriction, Ri; scarcity, Si) and functional rarities (uniqueness, Ui; distinctiveness, Di) were calculated for each species. Correlations between rarity indices verified whether taxonomically rare species are also functionally rare. Functional entities (FEs) characterized the functional redundancy of the assemblages. The taxonomic structure was compared between estuaries with NMDS and PERMANOVA. The functional structure was described by PCoA and characterized by functional richness (FRic) and dispersion (FDis) indices. Species loss simulations were carried out in order to find out how the most original and specialized species contribute to the functional structure of estuaries in terms of the FRic and FDis of the assemblages. A total of 126 species were collected in eight estuaries along the coast of Ceará. The records fill in 224 gaps for occurrences in individual estuaries. Many species were regionally restricted, in addition to presenting low variation in Ui and Di . The species were inserted in 44 EFs, of which thirty had less than three species, which makes about 30% of the species with low functional redundancy. The taxonomic composition was differentiated between groups of estuaries. Estuaries in a prolonged drought event lose less functional richness as the most original and specialized species are excluded. In conclusion, estuaries have few dominant species that are redundant and many rare species that tend to be more functionally distinct. In addition, they are environments of high functional redundancy, but still present a large part of the species set with little or no redundancy in many EFs. High salinity levels modify the taxonomic and functional structures of estuaries, which may be a consequence of marinization during extreme drought or hypersalinity events. This may have implications for the effects of climate change on these ecosystems. Thus, the present study provides subsidies for future research and conservation and management programs.